Polymorphism and taxonomic problems in the Perlodes microcephalus group (Plecoptera: Perlodidae); Perlodes mortoni removed from synonymy - Zwick, Peter (Illiesia, 2011)
Perlodes spp. of the microcephalus-group can presently be identified only by microscopic sclerites on the edge of the egg anchor. However, males from populations identified by egg structure have characteristic freqency distributions of relative wing lengths (RWL) which are helpful in species distinctions. Across its range, Perlodes dispar is uniform both with regard tomale RWL and egg anchor sclerites. Apart from a single small German population, P. microcephalus is uniform with regard to egg anchor sclerites, but polymorphic concerning male RWL. P. dispar and P. microcephalus are frequently sympatric biospecies. The allopatric Perlodes mortoni (Klapálek, 1906) from the British Isles is removed from synonymy with P. microcephalus (Pictet, 1833) and regarded as a distinct species. It resembles P. dispar by invariably micropterous males. The egg anchor sclerites differ from both other species but individual variation is so remarkable that no characteristic species standard can be described. The biospecies status of P. mortoni needs confirmation with other methods.
Keywords: entomology; Perlodes; entomologija; Perlodes mortoni; vrbnice; polimorfizem; polymorphism; brachypterism; egg anchor; sympatry; biospecies; Plecoptera